True or false? the impact of health-oriented leadership on work engagement in the hotel industry - Han, Yao; Mohamed, Rosmah (SAGE Publications, 2025)
The rebound of the global tourism industry highlights the importance of hotel employees’ work engagement, given their pivotal roles in service performance. While previous research has demonstrated the positive impact of health-oriented leadership (HOL) on employee engagement, few studies have examined the underlying mechanism and boundary conditions. An empirical analysis was conducted on four- and five star hotels in China, and 520 frontline employees were randomly selected from different hotels. Data were collected via online questionnaire, and the proposed model was tested using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4. The findings underscore that HOL has a positive impact on work engagement. Recovery experiences emerges as a pivotal mechanism mediating the relationship between HOL and work engagement. Furthermore, trust moderates the relationship between HOL and recovery experiences. High trust strengthens the relationship, while HOL and recovery experiences even have slightly negative relationship when the level of trust is low. This study contributes to the underlying and boundary mechanisms of the relationship from a recovery perspective.